A PRRT2 variant in a Chinese family with paroxysmal kinesigenic dyskinesia and benign familial infantile seizures results in loss of interaction with STX1B. (15th July 2018) - Ma, Hongying; Feng, Shenglei; Deng, Xuejun; Wang, Li; Zeng, Sheng; Wang, Cheng; Ma, Xixiang; Sun, Hao; Chen, Rui; Du, Shiyue; Mao, Jinglin; Zhang, Xianwei; et al.
Summary: Objective: To identify the causative gene of autosomal dominant paroxysmal kinesigenic dyskinesia and benign familial infantile seizures (PKD/BFIS) in a large Chinese family and explore the potential pathogenic mechanism of a PRRT2 (proline‐rich transmembrane protein 2) variant. Methods: Genetic testing was performed via whole exome sequencing. Western blotting and immunofluorescence were used to analyze the protein expression level and subcellular localization of the PRRT2 mutant in HeLa cells and N2A cells. Coimmunoprecipitation was conducted to investigate the interaction of the PRRT2 mutant with syntaxin 1B (STX1B). Results: In a large Chinese family with autosomal dominant PKD/BFIS showing wide phenotypic heterogeneity, including patients suffering from PKD, BFIS, or epilepsy and asymptomatic variant carriers, a c.621dupA variant in PRRT2 was identified in the proband and was shown to cosegregate with the phenotype in this family. This variant results in premature termination at codon 224, producing a truncated protein (p.Ser208Ilefs*17) in which the two conserved hydrophobic segments and the cytoplasmic loop are missing. Both the expression and subcellular localization of PRRT2 are strongly affected by the c.621dupA variant. In addition, we found that PRRT2 directly interacts with STX1B, a SNARE protein critical for neurotransmitter release, whereas the truncated variant p.Ser208Ilefs*17 lacking the helix‐loop‐helix domain fails to bind to STX1B. Significance: Our findings identified a PRRT2 variant in a family with PKD/BFIS and confirmed STX1B as a new binding partner of PRRT2, which suggested that the loss of the interaction between PRRT2 and STX1B may contribute to the pathogenesis of PKD/BFIS.